2020
DOI: 10.21608/asmj.2020.106416
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Mini Gastric Bypass as a Revisional Procedure After Failed Primary Restrictive Bariatric Surgery

Abstract: Background: Restrictive bariatric procedures are commonly performed to induce weight reduction, however, some patients may require a second surgery due to inadequate weight loss, weight regain or late complications. Laparoscopic mini gastric bypass (LMGB) is a promising bariatric procedure, which provides an effective long-term weight loss and resolution of primary procedure related complications. Aim of the Work: To assess laparoscopic Mini Gastric Bypass as a bariatric surgical technique for revision after f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In another study by Bhandari et al, the rate of remission was 100% for DM and HTN at 1 and 2-year follow-ups 5 . Another study showed remission of DM, HTN, DLP and GERD in 91.6%, 64.7%, 70.5% and 80% of patients at 1-year follow-up respectively 11 . Debs et al, showed the improvement/remission of DM, OSA and HTN in 76.9%, 81.8% and 82.6% of patients in 1–5 years follow-ups after conversion of SG to OAGB 23 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In another study by Bhandari et al, the rate of remission was 100% for DM and HTN at 1 and 2-year follow-ups 5 . Another study showed remission of DM, HTN, DLP and GERD in 91.6%, 64.7%, 70.5% and 80% of patients at 1-year follow-up respectively 11 . Debs et al, showed the improvement/remission of DM, OSA and HTN in 76.9%, 81.8% and 82.6% of patients in 1–5 years follow-ups after conversion of SG to OAGB 23 .…”
Section: Discussionmentioning
confidence: 91%
“…Some studies have shown controversial outcomes for related variables with different SG conversion procedures. There are limited published study about conversional OAGB following failed SG and most of them has reported the short to mid-term outcomes 9 11 that should be assess in long term.…”
Section: Introductionmentioning
confidence: 99%
“…25 A study by Chiappetta (2019) and her colleagues that compared between MGB and RYGB as a second step operation after SG showed that the causes of revision to MGB in 34 patients were inadequate weight loss in 64.7%, weight regain in 20.5% and GERD in 14.7%. 21 A study done by Sabry et al, (2020) that assessed the effect of MGB as a revisional procedure after failed primary restrictive bariatric surgery 23 Khoursheed, et al, (2013) published results revealed the mean operative time in r-RYGB was 161.2 min and the median hospital stay was 3 days. 24 Salama and Sabry (2016) published results on 60 patients that showed that the mean operative time of r-MGB after VBG was 145.41 minutes compared to 185.16 min with r-RYGB.…”
Section: Discussionmentioning
confidence: 99%